S100A9 as a Key Myocardial Injury Factor Interacting with ATP5 Exacerbates Mitochondrial Dysfunction and Oxidative Stress in Sepsis-Induced Cardiomyopathy - Pei H; Qu J; Chen J; Zhao G; Lu Z (Dove Medical Press, 2024)
Hui Pei,1 Jie Qu,1 Jianming Chen,1 Guangju Zhao,1 ZhongQiu Lu1,2 1Emergency Department, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, People's Republic of China; 2Wenzhou Key Laboratory of Emergency and Disaster Medicine, Wenzhou, People's Republic of ChinaCorrespondence: ZhongQiu Lu, Email lzq_640815@163.comPurpose: Sepsis-induced cardiomyopathy (SICM) is a prevalent cardiac dysfunction caused by sepsis. Mitochondrial dysfunction is a crucial pathogenic factor associated with adverse cardiovascular adverse events; however, research on SICM remains insufficient.Methods: To investigate the factors contributing to the pathological progression of SICM, we performed a comprehensive analysis of transcriptomic data from the GEO database using bioinformatics and machine learning techniques. CRISPR-Cas9 S100A9 knockout mice and primary cardiomyocytes were exposed to lipopolysaccharide to simulate SICM. Transcriptome analysis and mass spectrometry of primary cardiomyocytes were used to determine the potential pathogenic mechanisms of S100A9. The mitochondrial ultrastructure and mitochondrial membrane potential (MMP) were detected using transmission electron microscopy and flow cytometry, respectively. Pink1/Parkin and Drp1 proteins were detected using Western blotting to evaluate mitochondrial autophagy and division. The mtDNA and mRNA levels of mitochondrial transcription factors and synthases were evaluated using real-time polymerase chain reaction.Results: Bioinformatics analysis identified 12 common differentially expressed genes, including SERPINA3N, LCN2, MS4A6D, LRG1, OSMR, SOCS3, FCGR2b, S100A9, S100A8, CASP4, ABCA8A, and NFKBIZ. Significant S100A9 upregulation was closely associated with myocardial injury exacerbation and cardiac function deterioration. GSEA revealed that myocardial contractile function, oxidative stress, and mitochondrial function were significantly affected by S100A9. Knocking out S100A9 alleviates the inflammatory response and mitochondrial dysfunction. The interaction of S100A9 with ATP5 enhanced mitochondrial division and autophagy, inhibited MMP and ATP synthesis, and induced oxidative stress, which are related to the Nlrp3-Nfkb-Caspase1 and Drp1-Pink1-Parkin signaling pathways. The expression of mitochondrial transcription factors (TFAM and TFBM) and ATP synthetases (ATP6 and ATP8, as well as COX1, COX2, and COX3) was further suppressed by S100A9 in SICM. Targeted S100A9 inhibition by paquinimod partially reversed myocardial mitochondrial dysfunction and oxidative stress.Conclusion: The interaction of S100A9 with ATP5 exacerbates myocardial damage in sepsis by inducing mitochondrial dysfunction and oxidative stress. Keywords: S100A9, SICM, bioinformatics analysis, mitochondrial dysfunction, ATP5